Research of development and key technologies for mountainous rack railway - SONG Qingwei; WANG Yunpeng; WANG Shiqiang; NIE Xianpeng; YU Chunyang; XU Shilei (机车电传动)
The mountainous rack railway system currently becomes a hot topic in urgent need of research and development, under the backdrop of the development status quo and the application demands for rail transit systems in China, and in order to respond to the call for integrated development of “tourism + traffic + poverty alleviation” in mountainous regions. This paper mainly comprised the introduction on the features, development history and key technologies of rack railways, analysis on the application environment, and comprehensive elaboration on the key technologies from the aspects of the standard system, vehicle dynamics, driving and braking, and so forth. The rack railway system was designed with a ruling gradient up to 120‰ generally and even 250‰ at the maximum, and a negotiable radius of curve of 50 m to the minimum extent in the main line. Boasting the strong adaptation to the topographic conditions of mountainous lands, the rack railway system will certainly become a mainstream choice for the construction of mountainous tourism railways in China.